The holy anointing oil in Armenian tradition - Barker, Margaret 1944- (2018)
This article traces the link between the command given to Moses at Sinai to make the perfumed oil for the tabernacle and later the temple, and the complex Christian teaching about the oil. The meaning of temple furnishings and ritual was known only to the high priests, passed on by them to their heirs. These became some of the unwritten traditions known to Origen and St Basil. Since they were unwritten, the story has to be reconstructed from a variety of materials, none of which gives the complete picture, but all of them are related to the story of the holy oil. Later texts have many details whose consistency suggests that they had ancient roots, and so many apparently later developments can be shown to preserve the original temple practice.
Keywords: Armenian Apostolic Church; Holy Chrism (or muron); St. Gregory of Narek; Anointing; pope St Leo; priesthood of Aaron; Tree of life